Typologies of Learning Design and the introduction of a "LD-Type 2" case example - Dobozy, Eva (eLearning Europa, 2011)
This paper explores the need for greater clarity in the conceptualisation of Learning Design (LD). Building on Cameron’s (2010) work, a three-tiered LD architecture is introduced. It is argued that this conceptualisation is needed in order to advance the emerging field of LD as applied to education research. This classification differentiates between LD as a concept (LD Type 1), LD as a process (LD Type 2), and LD as a product (LD Type 3). The usefulness of the three types is illustrated by a case example of a virtual history fieldtrip module constructed in LAMS as Type 2 LD. This case shows the workflow from LD Type 1 to LD Type 2, followed by LD Type 3 research and development data. History as a learning area was chosen in this paper for its ability to illustrate LD concepts and the interrelationship of LD types. The case serves to illustrate the foundations, scope and ambitions of this learning design project, which was underpinned by an educational psychology framework and firmly linked to the goals of the new Australian curriculum. The purpose of LD as process is to inform other teachers of the affordance of LD, providing contextualised data and to invite critique of particular TEL practices.